Adsorption and Dissociation of CO(2) on Ru(0001) - Pachecka, M. (J Phys Chem C Nanomater Interfaces, 2017)
[Image: see text] The adsorption and dissociation of carbon dioxide on a Ru(0001) single crystal surface was investigated by reflection–absorption infrared spectroscopy (RAIRS) and temperature-programmed desorption (TPD) spectroscopy for CO(2) adsorbed at 85 K. RAIRS spectroscopy shows that the adsorption of CO(2) on a Ru(0001) single crystal is partially dissociative, resulting in CO(2) and CO. The CO vibrational mode was also observed to split into two distinct modes, indicating two general populations of CO present at the surface. Furthermore, a time-dependent blue-shift is observed, which is characteristic of increasing CO surface coverage. TPD showed that coverages of up to 0.3 ML were obtained, and no evidence for chemisorption of oxygen on ruthenium was found.